Effect of Magnetic Field on Plasma Engines - Ali, Hayder; Yaseen, Waleed Ibrahim (Iraqi Journal of Physics, 2025)
Ion engines, also known as plasma engines, are a pioneering space propulsion technology that is constantly being developed. In this work, a static magnetic field is used in a cylindrical engine that is placed inside a vacuum chamber under a pressure of 0.2 mbar and uses argon gas with an applied voltage of 5 kV and an engine power supply of 25-100 watts. The shape and intensity of the magnetic field determine the discharge performance of the ion thruster. A cylindrical ion engine was constructed with dimensions 5, 5.5, and 0.7 cm in length, width, and thickness, respectively. The coil of the ion engine generates a static magnetic field of 9 and 25 mT. This system was used to study the effect of the magnetic field on the ionization rate and plasma distribution. The results showed that the cylindrical magnetic field confined the energetic electrons primarily near the centre of the engine and resulted in an increased ionization rate in this region. The Langmuir probe is used to diagnose plasma parameters to calculate temperature and density with and without a magnetic field. The electron density in the centre of the ion engine increased in the presence of the magnetic field (2-6x1019) m-3, while the electron temperature decreased (2-4 eV). The use of a magnetic field contributes to reducing the energy consumption of the ion engine and reduces the energy expended to generate plasma inside the ion engine, making the use of the magnetic field in ion engines suitable for spacecraft.